Dual-Interface WiFi Packet Sniffer System using ESP32-CAM with Real-Time PCAP Generation for IoT Network Analysis - Setiawan, Boy, Boy; Maulani, Maghfiroh; Pratama Putra, Zico; Senoyodha Brennaf, Muhammad (Makara Journal of Technology, 2025)
This study focuses on designing and implementing a cost-effective and energy-efficient WiFi packet sniffer system using the ESP32. The ESP32-CAM module, which combines WiFi, Bluetooth, and microSD support, is used to capture IEEE 802.11 frames in real-time via promiscuous mode. Packets are stored in packet capture format, which is compatible with tools such as Wireshark and Scapy. Developed using the official ESP-IDF, it offers low-level control and high performance. Two user interfaces were implemented: a UART-based text menu and a web-based HTTPS menu hosted on the ESP32 itself. Functional and performance evaluations were conducted with a focus on capturing broadcast and management frames without payload decryption. The system achieves 99.99% packet capture accuracy at 500,000 packets with a total hardware cost of $25 and power consumption of 2.1 W during active capture, representing a 95% cost reduction and 80% power savings compared to commercial alternatives. The download and file-listing speeds through the web-based menu were also evaluated, revealing that the system performs optimally with fewer files but experiences interruptions during large-scale operations. The proposed system provides a lightweight, standalone, and highly portable alternative to conventional packet sniffing tools despite the limitations in encryption handling and resource constraints. This makes it suitable for educational, diagnostic, and preliminary network analysis, particularly in low-power scenarios.